MRI Tracking of SPIO- and Fth1-Labeled Bone Marrow Mesenchymal Stromal Cell Transplantation for Treatment of Stroke. (29th August 2019) - Huang, Xiaolei; Xue, Yang; Wu, Jinliang; Zhan, Qing; Zhao, Jiangmin
Abstract : We aimed to identify a suitable method for long-term monitoring of the migration and proliferation of mesenchymal stromal cells in stroke models of rats using ferritin transgene expression by magnetic resonance imaging (MRI). Bone marrow mesenchymal stromal cells (BMSCs) were transduced with a lentivirus containing a shuttle plasmid (pCDH-CMV-MCS-EF1-copGFP) carrying the ferritin heavy chain 1 ( Fth1 ) gene. Ferritin expression in stromal cells was evaluated with western blotting and immunofluorescent staining. The iron uptake of Fth1 -BMSCs was measured with Prussian blue staining. Following surgical introduction of middle cerebral artery occlusion, Fth1 -BMSCs and superparamagnetic iron oxide- (SPIO-) labeled BMSCs were injected through the internal jugular vein. The imaging and signal intensities were monitored by diffusion-weighted imaging (DWI), T2-weighted imaging (T2WI), and susceptibility-weighted imaging (SWI) in vitro and in vivo . Pathology was performed for comparison. We observed that the MRI signal intensity of SPIO-BMSCs gradually reduced over time. Fth1 -BMSCs showed the same signal intensity between 10 and 60 days. SWI showed hypointense lesions in the SPIO-BMSC (traceable for 30 d) and Fth1 -BMSC groups. T2WI was not sensitive enough to trace Fth1 -BMSCs. After transplantation, Prussian blue-stained cells were observed around the infarction area and in the infarction center in both transplantation models. Fth1 -BMSCs transplanted for treating focal cerebral infarction were safe, reliable, and traceable by MRI. Fth1 labeling was more stable and suitable than SPIO labeling for long-term tracking. SWI was more sensitive than T2W1 and suitable as the optimal MRI-tracking sequence.